CFD tool application in predicting the behavior of a centrifugal fan designed by one-dimensional theory (Research, Society and Development, 2021)
Computational fluid dynamics (CFD) is the most current technology in the fluid flow study. Experimental methods for predicting the turbomachinery performance involve greater time consumption and financial resources compared to the CFD approach. The purpose of this article is to present the analysis of CFD simulation results in a centrifugal fan. The impeller was calculated using the one-dimensional theory and the volute the principle of constant angular momentum. The ANSYS-CFX software was used for the simulation. The turbulence model adopted was the SST. The simulation provided the characteristic curves, the pressure and velocity distribution, and the static and total pressure values at impeller and volute exit. An analysis of the behavior of the pressure plots, and the loss and recovery of pressure in the volute was performed. The results indicated the characteristic curves, the pressure and velocity distribution were consistent with the turbomachinery theory. The pressure values showed the static pressure at volute exit was smaller than impeller exit for some flow rate. It caused the pressure recovery coefficient negative.  This work indicated to be possible design a centrifugal fan applying the one-dimensional theory and optimize it with the CFD tool.